Effectiveness of Using Audio Visual Media on Early Childhood Listening Ability - Mappapoleonro, Andi musda (JUPE : Jurnal Pendidikan Mandala, 2024)
This research was motivated by children's low interest in learning, which can be seen from the large number of children who do not pay attention to the teacher when speaking in front of the class and do not understand the material being presented. This research aims to obtain empirical data regarding the influence of the use of audio-visual media on the listening abilities of young children at TK Putra VI Pasar Friday, Pondok Pinang, in the 2022-2023 school year. This research uses a quantitative approach with experimental methods. The research population included all students at Putra VI Kindergarten in Pasar Friday, Pondok Pinang, Kebayoran Lama District, South Jakarta. The research sample consisted of 10 students selected using random sampling techniques. This research involved pretest (before treatment) and posttest (after treatment) measurements. Data was collected using a questionnaire or questionnaire. Based on the results of the analysis, the data before treatment showed a mean of 23.3, a median of 26.5, a mode of 20.9, and a standard deviation of 5.35. After treatment, the data showed an increase with a mean of 27.4, median of 33.5, mode of 26.3, and standard deviation of 5.06. The results of the hypothesis test show that the value of tcount=3.15t \text{count} = 3.15tcount=3.15 is greater than ttable=1.83t \text{table} = 1.83ttable=1.83. Thus, H₁ is accepted and H₀ is rejected. This research concludes that there is a significant influence from the use of audio-visual media on the listening ability of children aged 5-6 years, Kindergarten Putra VI Pasar Friday, Pondok Pinang, Kebayoran Lama District, South Jakarta.